Perlindungan Hukum Terhadap Konsumen Atas Keamanan Pangan Oleh Badan Pengawas Obat dan Makanan - Bafadhal, Faizah; Alissa, Evalina; Idris, Isran (Universitas Jambi, Fakultas Hukum, 2024)
Food is a basic human need that cannot be neglected in everyday life. Without eating and drinking sufficient quantity and quality, humans will not be productive in carrying out their activities. Food issues also concern security, safety, and health, both physical and spiritual. Food safety is one of the important factors that must be considered in daily consumption. Thus, food must be available in sufficient quantities, at affordable prices, and must also meet other requirements, namely healthy, safe, and halal. So before the food is distributed it must meet the requirements of being truly safe for consumption. This means that food must not contain dangerous ingredients such as pesticide contamination, heavy metals, pathogen microbes, or be contaminated by ingredients that could disturb people's trust or confidence, for example being contaminated with dangerous ingredients. Food security in Indonesia is still far from safe, which can be seen from the food poisoning incidents that have occurred recently. In such conditions, consumers generally do not care or do not have awareness about the safety of the food they consume, so they do not demand much from producers to produce safe food products. This also causes food producers to increasingly ignore consumer safety in order to gain as much profit as possible. For example, there are still many food manufacturers who like to use textile dyes for various food and beverage products because of economic considerations.